Variations in yeast plasma‐membrane lipid composition affect killing activity of three families of insect antifungal peptides. (14th August 2019) - Kodedová, Marie; Valachovič, Martin; Csáky, Zsófia; Sychrová, Hana
Abstract: Naturally occurring antimicrobial peptides and their synthetic analogues are promising candidates for new antifungal drugs. We focused on three groups of peptides isolated from the venom of bees and their synthetic analogues (lasioglossins, halictines and hylanines), which all rapidly permeabilised the plasma membrane. We compared peptides' potency against six pathogenic Candida species ( C. albicans, C. glabrata, C. parapsilosis, C. tropicalis, C. krusei and C. dubliniensis ) and the non‐pathogenic model yeast Saccharomyces cerevisiae . Their activity was independent of the presence of the multidrug‐resistant pumps of C. glabrata but was influenced by the lipid composition of cell plasma membranes. Although the direct interaction of the peptides with ergosterol was negligible in comparison with amphotericin B, the diminished ergosterol content after terbinafine pretreatment resulted in an increased resistance of C. glabrata to the peptides. The tested peptides strongly interacted with phosphatidylglycerol, phosphatidic acid and cardiolipin and partly with phosphatidylinositol and phosphatidylethanolamine. The interactions between predominantly anionic phospholipids and cationic peptides indicated a mainly electrostatic binding of peptides to the membranes. The results obtained also pointed to a considerable role of the components of lipid rafts (composed from sphingolipids and ergosterol) in the interaction of yeast cells with the peptides.